RETRACTED: Evaluation of the safety of retroperitoneal laparoscopic partial nephrectomy by investigating the perioperative indicators - Zhang, Xiaoyan; Xing, TianJun (Frontiers in Oncology, 2023)
Background: In recent years, open nephron sparing partial nephrectomy (OPN) has been gradually applied and generally accepted. Recent statistical data show that PN not only can safely and effectively preserve the functional nephron, but also has fewer complications, low local recurrence rate and no significant difference in long-term survival rate compared with nephrectomy/radical nephrectomy, which has gradually become a routine treatment for small renal cell carcinoma.herefore, how to maximize the protection of postoperative residual renal function (RRF) and reduce the risk of CKD while achieving the ideal local and overall tumor control effect is the key to the treatment of renal cancer, and is also the focus of attention of urologists and nephrologists. Objective: To evaluate the safety of retroperitoneal laparoscopic partial nephrectomy (RLPN) by investigating the perioperative indicators and postoperative follow-up. Methods: A total of 20 hospitalized patients in our hospital from December 2019 to December 2021 were selected and followed up for a long time. Patients with renal tumors less than 4cm in diameter and exogeneous or partial exogeneity were randomly divided into 2 groups. Patients in retroperitoneal laparoscopic group (n = 20) were treated with nephron sparing partial nephrectomy (0.5-1cm). The time of removal of drainage tube, drainage volume, time of feeding activity and postoperative hospital stay were recorded, and the safety of the operation was evaluated. Conclusion: The perioperative safety and short-term postoperative renal function recovery of RLPN are good, and the overall safety of this operation is worthy of affirmation.